CLINICAL AND MICROBIOLOGICAL PROFILE OF PATIENTS ADMITTED WITH PNEUMONIA PRESENTING TO A TERTIARY CARE HOSPITAL IN SOUTHERN RAJASTHAN - AMIT SATISH GUPTA; HARSH SHARMA; VIDUSHI MEEL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Pneumonia is a leading cause of morbidity and mortality in India. This study was conducted to understand the clinical and microbiological profile of pneumonia patients presenting to our hospital and also to understand the resistance pattern among them. Methods: It was a retrospective observational study. Duration of the study was 6 months (June 2023 to December 2023). All patients admitted with a diagnosis of pneumonia (CAP, HAP, VAP) were included in the study and data was collected from previous medical records. Only those patients with pneumonia whose sputum or BAL (bronchoalveolar lavage) culture was positive for an organism were included in the study. Results: A total of 50 patients with pneumonia were included the study. Majority of the patients were males (72 %) with average age of 62. Community acquired pneumonia was diagnosed in 21 patients, hospital acquired pneumonia in 15 patients and ventilator associated pneumonia in 14 patients. Most common organism isolated was Klebsiella pneumoniae (36 %), followed by Acinetobacter baumannii (24 %), pseudomonas aeruginosa (16 %), E.coli (10 %) and others (14 %). Organisms isolated from hospital and ventilator associated pneumonia showed higher prevalence of carbapenem resistance than those isolated from community acquired pneumonia patients. Conclusion: Klebsiella pneumoniae was the most common organism isolated in CAP, HAP and VAP patients in our study. The resistance pattern of Klebsiella pneumoniae showed higher prevalence of carbapenem resistance in hospital and ventilator associated pneumonia patients as compared to CAP patients. Keywords: Pneumonia, Hospital acquired pneumonia, Ventilator Associated pneumonia, Klebsiella pneumoniae